Uji Ketinggian dan Tipe Perangkap untuk Mengendalikan Penggerek Buah Kopi (Hypothenemus hampei Ferr.) (Coleoptera : Scolytidae) di Desa Pearung Kabupaten Humbang Hasundutan - Kreniva Megawati Sinaga; Darma Bakti; Mukhtar Iskandar Pinem (Jurnal Agroekoteknologi, 2015)
This research aims to know the efective height and type of trap which is most attack H. hampei in the field. The research was held at Pearung village, Sub-district Paranginan, District Humbang Hasundutan, North Sumatera from September until October 2014. The method used Randomized Block Design with two factors and three replications. The first factor was height of trap (1.0 ; 1.2 ; 1.4 ; 1.6 and 1.8 m) and the second factor was the type of trap (single funnel trap, multiple funnel trap, and mineral bottle). The results showed that the best trap was 1.2 m + multiple funnel trap, and the highest symptom percentage was 1.0 m + single funnel trap.Keywords : height, trapping, Hypothenemus hampei Ferr.